Improving Mathematics Teachers’ Skills in Designing Context-based Tasks for Lower Secondary School Learning - Sri Rejeki; Christina Kartika Sari; Muhamad Toyib; Meladia Salsabila Ulfah (Indonesian Journal of Community Services, 2022)
Using context-based problems is essential to mathematics learning, especially with implementing the Minimum Competency Assessment or Asesmen Kompetensi Minimum (AKM). However, this has not been supported by learning resources that provide context-based math problems optimally. Therefore, there is a need for efforts to improve the skills of mathematics teachers in designing context-based problems. This community service or Pengabdian kepada Masyarakat (PkM) activity aims to enhance teachers' skills in designing context-based math problems based on numeracy AKM. This PkM activity was carried out as training involving ten mathematics teachers of Muhammadiyah Junior High School (SMP) in Kartasura District, Sukoharjo Regency, Central Java, Indonesia as training participants. In the first stage, the training was conducted online via Zoom Video Conference. Furthermore, the second phase of the activity focused on assisting the teachers of the training participants in compiling context-based junior high school math problems in numeracy AKM, especially on number content. The assistance was carried out using the Schoology Learning Management System (LMS). The results of PkM showed that based on the post-training survey, 75% of participants stated that they understood the concept of numeracy AKM and 100% of participants were ready to integrate numeracy AKM in the implementation and assessment of mathematics learning, especially in number content. The achievement of PkM targets is also reflected in training products as a collection of AKM-oriented mathematics problems on number content. Furthermore, further assistance is needed, focusing on the design of AKM context-based questions on geometry, algebra, and statistical content.